2021
DOI: 10.1136/bmjopen-2021-049640
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges of fetal heart function using a Modified Myocardial Performance Index: a prospective multicentre, cross-sectional study

Abstract: ObjectivesThe primary aim of this study was to establish the normal reference ranges of the fetal left ventricular (LV) Modified Myocardial Performance Index (Mod-MPI). A secondary aim was to evaluate the agreement between manual and automatic measurements for fetal Mod-MPI.DesignA prospective, multicentre, cross-sectional study.ParticipantsNormal singleton pregnancies.MethodsThe LV functions of normal singleton pregnancies were assessed in nine centres covering eight provinces in China using unified ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The increase in mod-MPI over gestation is also consistent with most manuscripts reporting left mod-MPI reference ranges but not meeting our inclusion criteria [21][22][23]. However, a few other studies reported either a negative or no correlation between mod-MPI and gestational age [24,25].…”
Section: Discussionsupporting
confidence: 86%
“…The increase in mod-MPI over gestation is also consistent with most manuscripts reporting left mod-MPI reference ranges but not meeting our inclusion criteria [21][22][23]. However, a few other studies reported either a negative or no correlation between mod-MPI and gestational age [24,25].…”
Section: Discussionsupporting
confidence: 86%
“…As a result of the highly heterogeneous measurement techniques used so far, with priority given to the lack of standard criteria regarding caliper placement, clinicians are currently confronted with a wide variation in the quoted reference values for the MPI to date-which still lack consistency-ranging from 0.35 to 0.60 as the mean values. The values of the RV-Mod-MPI for both operators corresponded with this expected distribution pattern and increased with GA (Figure 3), even though a significant correlation between the MPI and GA has been controversially discussed in the current literature [1,8,15,18,20,23,[26][27][28][29][30][31][32][33]. The present values of the RV-Mod-MPI were very similar to those of Kang et al, who investigated the clinical value of the MPI+™ tool for the assessment of cardiac function in TTTS.…”
Section: Discussionsupporting
confidence: 86%
“…There is a wide variation in the quoted reference values of the MPI to date-which are still inconsistent-ranging from 0.35 to 0.60 as the mean values. Therefore, a significant correlation between the MPI and the gestational age (GA) is controversially debated in the current literature [1,8,15,18,20,23,[26][27][28][29][30][31][32][33]. The Mod-MPI is less dependent on factors that impair image acquisition and quality than the other methods used for assessing fetal cardiac function (e.g., maternal BMI, anterior placenta, oligohydramnios), is less dependent on fetal anatomy and position or precise imaging and, by incorporating only time intervals, is less prone to artifacts such as fetal movements.…”
Section: Introductionmentioning
confidence: 99%
“…There is no universal reference range and guidelines for normal Mod-MPI values. Normal reference ranges of fetal Mod-MPI still show wide variations in recent studies, 29 - 33 reported due to heterogeneous study populations, possibly other maternal or fetal characteristics, and differences in measurement techniques. Comparable 29 , 31 , 32 or totally different 30 , 33 Mod-MPI values from ours have been cited in the literature.…”
Section: Discussionmentioning
confidence: 98%